EFEKTIVITAS PEMBELAJARAN TATAP MUKA (PTM) TERBATAS TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPA DAN PRAKTIKUMNYA DITINJAU DARI KEMANDIRIAN SISWA - Siti Darmawati; Kasliyanto Kasliyanto; Abdullah Derlean (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
The purpose of this study is to determine (1) the difference in the effect between face-to-face learning is limited to science learning accompanied by practicum and without practicum on student learning outcomes; (2) the difference in the effect between high, medium, low learning outcomes on student learning outcomes; and (3) the interaction between learning independence and science learning using practicum on student learning outcomes in limited face-to-face learning. This research was carried out in class VII of SMP Negeri 13 Maluku Tengah for the 2021 academic year, with a population of 132 students. Sampling is carried out by random sampling. Homogeneity test using Levene's Test. Hypothesis testing using Independent Samples T Test, K Independent Samples T Test, Linear Regression with the help of the Statistical Package for Social Sciense (SPSS) program version 23.0. based on the results of the analysis, the conclusion was reached that, (1) there are differences in the effect of limited face-to-face learning on science learning accompanied by practicum and without practicum on student learning outcomes; (2) there are differences in science learning outcomes between students who have high, medium, and low independence; and (3) there is an interaction of learning independence with science learning using practicum on student learning outcomes in limited face-to-face learning.